2016
DOI: 10.1002/jor.23277
|View full text |Cite
|
Sign up to set email alerts
|

Baseline cartilage quality is associated with voxel‐based T and T2 following ACL reconstruction: A multicenter pilot study

Abstract: In this multi-center study, voxel-based relaxometry (VBR), a novel technique to automatically quantify localized cartilage change, was used to investigate T and T relaxation times of patients with anterior cruciate ligament (ACL) tears at the time of injury and 6 months after reconstructive surgery. Sixty-four ACL-injured patients from three sites underwent bilateral 3T MR T and T mapping; 56 patients returned 6 months after surgery. Cross-sectional and longitudinal VBR comparisons of relaxation times were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…OA subjects showed elevation in the central weight-bearing area of the lateral tibia, while subjects after ACL reconstruction demonstrated a more posteriorly located elevation. Russell et al (22) recently studied the T 1ρ longitudinal progression in ACL subjects using VBR, and showed a similar effect of shifting elevation in lateral tibia between baseline and 6 months after ACL reconstruction. When the elevation was observed in the most posterior aspect of the lateral tibia at baseline, the elevation was more anteriorly located at 6 months.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…OA subjects showed elevation in the central weight-bearing area of the lateral tibia, while subjects after ACL reconstruction demonstrated a more posteriorly located elevation. Russell et al (22) recently studied the T 1ρ longitudinal progression in ACL subjects using VBR, and showed a similar effect of shifting elevation in lateral tibia between baseline and 6 months after ACL reconstruction. When the elevation was observed in the most posterior aspect of the lateral tibia at baseline, the elevation was more anteriorly located at 6 months.…”
Section: Discussionmentioning
confidence: 85%
“…This technique allows for the investigation of local cartilage composition differences between two groups through voxel-based statistical parametric mapping (SPM). VBR and SPM were recently used in a multicenter study that aimed to explore how cartilage lesions at the time of ACL injury influence the longitudinal progression of cartilage degeneration (22), while a related study explored the usage of the composite R 2 -R 1ρ metric as a possible associative biomarker for patientreported outcomes (23).…”
Section: Introductionmentioning
confidence: 99%
“…This prior study demonstrated that VBR was feasible and consistent with traditional ROI‐based analysis in the knee joint. VBR has also showed promising results in a study which evaluated the contribution of cartilage lesions to the longitudinal progression of T 1ρ and T 2 after ACL reconstruction in a multi‐center study …”
mentioning
confidence: 99%
“…In the later study, mechanical tests revealed a 19% increase in tibial articular cartilage thickness 3 months after injury and this supports our finding of a 14% increase in thickness (calculated as a mean increase in thickness of 0.4 mm relative to a mean 2.8 mm thick cartilage obtained from normal knees at the same location). Our measurements were taken soon after injury (mean 17 days) and are concerning as there is a strong evidence that the articular cartilage and its matrix components change soon after ACL injury, reconstruction and return to activity . In addition, following severe knee trauma that involves the ACL, increased T1ρ and T2 relaxation times are thought to reflect loss of proteoglycan and change in water content that precede changes to cartilage thickness associated with the progression of PTOA.…”
Section: Discussionmentioning
confidence: 99%